FORMULATION AND IN-VITRO EVALUATION OF MIRABEGRON EXTENDED-RELEASE TABLETS USING HPMC - Chandra Prakash Sunuwar , Meenakshi Kandwal , Shivanand Patil (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
The current investigation centered on the development and in vitro assessment of extended release (ER) tablets of Mirabegron utilizing Hydroxypropyl Methylcellulose (HPMC) as the polymer for controlling release. Mirabegron, which acts as a β3-adrenergic receptor agonist, is prescribed for the management of overactive bladder syndrome. The objective was to develop an extended release formulation that ensures prolonged drug release, improved patient compliance, and consistent plasma drug levels. Nine formulations (F1–F9) were prepared using various grades and concentrations of HPMC (K4M, K100M, and K100LV) and evaluated for pre-compression, post-compression, and in vitro drug release parameters. Fourier Transform Infrared (FTIR) analysis confirmed the absence of interactions between Mirabegron and excipients, ensuring formulation stability. The pre-compression evaluations confirmed favourable flow properties with a Carr’s Index range of 18.33–24.50% and an angle of repose between 25.17° and 29.68°. Analyses conducted after compression showed that all formulations complied with the pharmacopeial criteria for weight uniformity, hardness, friability, and thickness. Drug release profiles revealed significant variations, with formulation F9 showing optimal sustained release characteristics, achieving 92.88% drug release over 7 hours with zero-order kinetics. This study highlights the potential of hydrophilic matrix systems in achieving controlled drug release. The findings pave the way for developing effective extended release formulations, offering therapeutic benefits such as reduced dosing frequency, enhanced treatment adherence, and improved management of chronic conditions like overactive bladder syndrome. Future studies should focus on in vivo evaluations and scale-up for commercial production.